Strategies and prospects for melatonin to alleviate abiotic stress in horticultural plants - Xiaoyun Wang; Meng Cao; Hongxin Li; Ying Liu; Shuangxi Fan; Na Zhang; Yangdong Guo (Horticultural Plant Journal, 2024)
Melatonin is a conserved pleiotropic molecule in animals and plants. Melatonin is involved in many development processes and stress responses; thus, exploring its function in plants, particularly in horticultural plants, has become a rapidly developing field. Many studies have revealed that phytomelatonin acts as a plant biostimulant and increase its tolerance to various abiotic stressors, including extreme temperature, drought, osmotic disturbance, heavy metals, and ultraviolet (UV). Melatonin appears to have roles in the scavenging of reactive oxygen species (ROS) and other free radicals, affecting the primary and secondary metabolism of plants, regulating the transcripts of stress-related enzymes and transcription factors, and crosstalk with other hormones under different environmental conditions. This pleiotropy makes phytomelatonin an attractive regulator to improve resistance to abiotic stress in plants. The recent discovery of the potential phytomelatonin receptor CAND2/PMTR1 and the proposition of putative models related to the phytomelatonin signaling pathways makes phytomelatonin a new plant hormone. Based on relevant studies from our laboratory, this review summarizes the phytomelatonin biosynthetic and metabolic pathways in plants and the latest research progress on phytomelatonin in abiotic stress of horticultural plants. This study will provide a reference for elucidating the regulatory mechanism of phytomelatonin affecting the resistance to abiotic stress in plants.